Residential Mobility di Pinggiran Kota Semarang Jawa Tengah (Studi Kasus Kaum Miskin Kota di Kota Semarang) - Rindarjono, Moh. Gamal (Forum Geografi, 2007)
This research was aimed in analyzing and examining the development of slum residential in Semarang, including its center of the city urban, urban-fringe and sub-urban area. Within the development of the slum residentialÂ due to mobility of the urban poor, the phenomenon in the term of residential mobility occurred. Using both qualitative and quantitative methods, this research was applying distant-interpretation data in examining slum residential phenomenon and terrestrial data in analyzing both social and cultural issues related to development of slum residential. This research resulting a residential mobility model throughout areas of research, especially sub-urban including the Chinese cemetery area; the new migrant was the urbanist namely the bridge headers group, consists of tramp and hobos whom should be concerned more. Though they just have settled in short-period within the area, their income was categorized financially settled. They owned their own home not as the renter and even, built housing for their subordinates amounted 7-15 families in a complex of residential. Stability of the income was also supported by resident-owning whereas selecting its location based on the land-availability which initially settled the location illegally among the graves. This location was selected since its less-maintained condition by neither their descendant nor cemetery officer which then densely covered by bushes. Availability of the sufficient land leads them to build their residential which also used as the scrap collection space. During the times, their number was increased referred to their raising income. Legalizing their residential was the next step for their existence and sustainability by purchasing or renting the land. Eventually this bridge header was earning a stable income, owning their own home, and locating their residential in the sub-urban area furthermore but unfortunately less-supported by a highly established life style but an early category one . These were indicated by several factors, either employer or subordinate tramps which cooking foods altogether, unfashionably worn, and behavior of their youngster of asking consideration and advice to the consolidator and status seeker.